The Icing Characteristics of Post Insulators in a Natural Icing Environment - Zhijin Zhang; Jiahui Tu; Yuanpeng Zhang; Xingliang Jiang; Zhenbing Zhu (Atmosphere)
Icing significantly reduces the electrical performance of insulators, and grid failures caused by insulator icing are common. Currently, most research on the flashover characteristics of insulators under icing conditions focuses on artificially iced suspension insulators, with limited studies on post insulators under natural icing conditions. The shed spacing of post insulators is smaller, making them more prone to bridging by icicles in the same icing environment, which exacerbates insulation problems. Therefore, investigating the icing characteristics of post insulators is crucial. In this study, natural icing growth was observed on seven different types of post insulators at the Xuefeng Mountain Energy Equipment Safety National Observation and Research Station. The icing morphology and characteristics of these insulators were examined. The main conclusions are as follows: (1) the icing type and morphology of post insulators are influenced by meteorological conditions, with more severe icing observed on the windward side. (2) The icing mass and icicle length of the insulator increase nonlinearly with icing time. Specifically, during the glaze icing period from 0 to 8 h, the ice mass on the Type V composite post insulator was 3.89 times greater than that during the 13-to-18 h period. (3) Within the same icing cycle, the icing growth rate on composite post insulators is faster than on porcelain post insulators. (4) Compared to suspension insulators, the sheds of post insulators are more easily bridged by icicles. Notably, when the sheds of post insulators are bridged by icicles, the length of icicles on suspension insulators is only half of the gap size.